PENGARUH GROWTH ASSET DAN PROFITABILITAS TERHADAP STRUKTUR MODAL STUDI PADA PERUSAHAAN REAL ESTATE AND PROPERTY YANG LISTING DI BURSA EFEK INDONESIA - Monika Elvionita; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to test partially and simultaneously the influence of Growth Assets and Profitability on Capital Structure. Where the independent variable in this study is Growth Asset, Profitability and while the dependent variable is Capital Structure. The sample used is secondary data derived from the financial statements of real estate and property companies listed on the Stock Exchange in the period 2015-2017. This study uses secondary data in the form of company financial statements and annual reports of real estate and property companies listed on the Stock Exchange in the period 2015-2017. Sampling using purposive sampling technique, which is used is 28 companies. Data analysis using simple linear analysis, multiple linear regression, t test, f test and coefficient of determination test using SPSS 16 device. The results of this analysis indicate that the growth asset variable partially (t test) does not significantly influence the capital structure of real estate and property companies listed on the Indonesia Stock Exchange, the variable profitability partially (t test) does not significantly influence the capital structure of real estate companies and property listed on the Indonesia Stock Exchange. The simultaneous test results (f test) show that there is no effect of the variable growth assets and profitability on the capital structure of real estate and property companies listed on the Indonesia Stock Exchange. Keyword : Growth Asset, Profitability and Capital Structure